From Antibacterial to Antibiofilm Targeting: An Emerging Paradigm Shift in the Development of Quaternary Ammonium Compounds (QACs) - Saverina, Evgeniya A.; Frolov, Nikita A.; Kamanina, Olga A.; Arlyapov, Vyacheslav A.; Vereshchagin, Anatoly N.; Ananikov, Valentine P. (ACS infectious diseases, 2023)
In a previous development stage, mostly individual antibacterial activity was a target in the optimization of biologically active compounds and antiseptic agents. Although this targeting is still valuable, a new trend has appeared since the discovery of superhigh resistance of bacterial cells upon their aggregation into groups. Indeed, it is now well established that the great majority of pathogenic germs are found in the environment as surface-associated microbial communities called biofilms. The protective properties of biofilms and microbial resistance, even to high concentrations of biocides, cause many chronic infections in medical settings and lead to serious economic losses in various areas. A paradigm shift from individual bacterial targeting to also affecting more complex cellular frameworks is taking place and involves multiple strategies for combating biofilms with compounds that are effective at different stages of microbiome formation. Quaternary ammonium compounds (QACs) play a key role in many of these treatments and prophylactic techniques on the basis of both the use of individual antibacterial agents and combination technologies. In this review, we summarize the literature data on the effectiveness of using commercially available and newly synthesized QACs, as well as synergistic treatment techniques based on them. As an important focus, techniques for developing and applying antimicrobial coatings that prevent the formation of biofilms on various surfaces over time are discussed. The information analyzed in this review will be useful to researchers and engineers working in many fields, including the development of a new generation of applied materials; understanding biofilm surface growth; and conducting research in medical, pharmaceutical, and materials sciences. Although regular studies of antibacterial activity are still widely conducted, a promising new trend is also to evaluate antibiofilm activity in a comprehensive study in order to meet the current requirements for the development of highly needed practical applications.